1953
DOI: 10.1099/00221287-8-3-333
|View full text |Cite
|
Sign up to set email alerts
|

Factors governing the Toxicity of Cultures containing the Phytoflagellate Prymnesium parvum Carter

Abstract: SUMMARY: Methods for the laboratory maintenance and purification of cultures of Prymnesium parvum are detailed. The upper limit of temperature for the growth of the organism is 30". Light exerts an augmenting effect on the production of the toxin by Pr. paruum. Rapid and economical procedures for the bioassay of the toxin are based on the use of Gambusia minnows or tadpoles. Cell-free centrifugates of the cultures contain heat-labile toxic material which is non-diffusible through cellophan, sensitive to oxidiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

1964
1964
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(61 citation statements)
references
References 8 publications
2
59
0
Order By: Relevance
“…This could explain why different strains of P. parvum express different toxicities [9] and could be the reason for the discrepancy between the results reported in this study (strain: UTEX-2797) and those previously reported by Bergmann et al [41] for an unknown strain. Furthermore, observed P. parvum toxicity is sensitive to handling [44] and the composition of the aquatic environment [43]. Lastly, the material used in the experimental setup affects observed toxicity as well, as prymnesins readily bind to polymeric surfaces (log d = 3.4-5.2) [60].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could explain why different strains of P. parvum express different toxicities [9] and could be the reason for the discrepancy between the results reported in this study (strain: UTEX-2797) and those previously reported by Bergmann et al [41] for an unknown strain. Furthermore, observed P. parvum toxicity is sensitive to handling [44] and the composition of the aquatic environment [43]. Lastly, the material used in the experimental setup affects observed toxicity as well, as prymnesins readily bind to polymeric surfaces (log d = 3.4-5.2) [60].…”
Section: Discussionmentioning
confidence: 99%
“…At the time of the experiment, the proposed toxins (the prymnesins [38]), were unquantifiable [39,40]. Whether prymnesins are the sole toxins in a P. parvum bloom is debatable, so controlling for prymnesin content might confound the effects of other unknown toxins [7,8,[40][41][42][43]. Significant variations in toxicity have been reported when exposing fish externally to P. parvum culture [8,40].…”
Section: Algae Culture and Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Studying the characteristics of P. parvum has been motivated by the large economic losses it has caused, especially in fish farms (Edvardsen & Paasche 1998). P. parvum damages fish by destroying their gills (Yariv & Hestrin 1961, Shilo 1971 through toxins the cells excrete into the water (Shilo & Aschner 1953, Shilo & Rosenberger 1960. Taxonomical research suggests that haptophytes P. parvum and P. patelliferum represent different generations rather than separate gene pools, both belonging to the species P. parvum (Larsen 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Blooms are characterized by their seasonal recurrence, rapid proliferation, wide salinity and temperature tolerance, as well as the production of highly potent ichthyotoxins, the chemical nature of which remains incompletely known [5][6][7]. Recurring Prymnesium parvum blooms have become a routine problem for the Israeli Tilapia [8,9], the Texas striped bass [4,5] and, more recently, (June/July, 2009) the barramundi (Lates calcarifer) pond-based aquaculture industry in tropical Australia [2].…”
Section: Introductionmentioning
confidence: 99%